2015
DOI: 10.3390/md13106489
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids with Cardiovascular Effects from the Marine-Derived Fungus Penicillium expansum Y32

Abstract: Three new alkaloids (1, 4 and 8), together with nine known analogues (2, 3, 5–7, and 9–12), were isolated from the marine-derived fungus Penicillium expansum Y32. Their structures including the absolute configurations were elucidated by spectroscopic and Mosher’s and Marfey’s methods, along with quantum electronic circular dichroism (ECD) calculations. Each of the compounds was evaluated for cardiovascular effects in a live zebrafish model. All of the compounds showed a significant mitigative effect on bradyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Insect neurotoxicity was also observed in assays carried out on larvae of the bluebottle fly ( Calliphora vomitoria ) [ 94 ]. Moreover, in a study employing a zebra-fish model, communesin I and two more novel compounds, fumiquinazoline Q and protuboxepin E, were reported for cardiotonic effects, as well as some extent of vasculogenetic properties assessed with reference to both number and length of vessels [ 168 ].…”
Section: Bioactivities Of Novel Compoundsmentioning
confidence: 99%
“…Insect neurotoxicity was also observed in assays carried out on larvae of the bluebottle fly ( Calliphora vomitoria ) [ 94 ]. Moreover, in a study employing a zebra-fish model, communesin I and two more novel compounds, fumiquinazoline Q and protuboxepin E, were reported for cardiotonic effects, as well as some extent of vasculogenetic properties assessed with reference to both number and length of vessels [ 168 ].…”
Section: Bioactivities Of Novel Compoundsmentioning
confidence: 99%
“…Typical signals for oxepins were not observed in the NMR spectra of 3. Extensive interpretation of the spectroscopic data including NMR and CD spectra and comparison with known compounds 16 proved 3 to be protuboxepin K, a quinazolinone derivative of Ant, D-Phe, and L-Ile (Fig. 3) 17 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, isopropylchaetominine (324) was isolated, which showed strong cytotoxicity against the mouse lymphoma cell line L5178Y with an IC 50 value of 0.4 μmol/L (Özkaya et al 2018). Fumiquinazoline Q (325), isolated from the marine-derived fungus P. expansum Y32, exhibited potent vasculogenetic activity in vasculogenesis experiments, which suggested that it could be a promising candidate for cardiovascular disease lead compound (Fan et al 2015).…”
Section: Quinazoline-containing Indole Alkaloidsmentioning
confidence: 99%